2020
DOI: 10.1007/s40620-020-00812-2
|View full text |Cite
|
Sign up to set email alerts
|

Remote monitoring in peritoneal dialysis: benefits on clinical outcomes and on quality of life

Abstract: Background Automated peritoneal dialysis (APD) has been proved benefit from remote monitoring (RM), but evidences are limited. In this study, we compared clinical outcomes and quality of life (QoL) in two group of patients undergoing APD, with and without exposure of RM. Methods This is a retrospective cohort study, comparing outcomes in two groups of APD patients monitored during 6 months with RM (group A: n = 35) or standard care (group B: n = 38 patients). In our clinical practice, we assign the RM system t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
84
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(107 citation statements)
references
References 32 publications
2
84
0
Order By: Relevance
“…Secondly, the KDQOL-SF scale is an instrument developed for patients with chronic kidney disease, but no specific questions assess the effect of home dialysis monitoring daily activities and patient satisfaction. In 2020, Manani et al [ 15 ] detected similar results in patients with RPM with APD in accordance with a previous systematic review. Unlike other studies, they designed an internal questionnaire to evaluate the effect of RPM on HRQoL to a greater extent, and found that RPM–APD indicated an excellent acceptance and satisfaction when monitored closely and frequently.…”
Section: Quality Of Lifesupporting
confidence: 78%
See 3 more Smart Citations
“…Secondly, the KDQOL-SF scale is an instrument developed for patients with chronic kidney disease, but no specific questions assess the effect of home dialysis monitoring daily activities and patient satisfaction. In 2020, Manani et al [ 15 ] detected similar results in patients with RPM with APD in accordance with a previous systematic review. Unlike other studies, they designed an internal questionnaire to evaluate the effect of RPM on HRQoL to a greater extent, and found that RPM–APD indicated an excellent acceptance and satisfaction when monitored closely and frequently.…”
Section: Quality Of Lifesupporting
confidence: 78%
“…One of the main advantages of integrating RPM to APD is increased treatment adherence, and it is known that non-adherence to treatment is associated with more frequent peritonitis episodes [ 7 , 27 , 30 ]. However, current data in the literature contain conflicting results regarding the effect of RPM programs with APD on the frequency of peritonitis episodes, but, in general, RPM had no significant effect on the development of peritonitis [ 6 , 10 , 11 , 15 ]. While Sanabria et al [ 6 ] reported fewer peritonitis episodes in patients with RPM than those without RPM, Manani et al [ 15 ] and Corzo et al [ 11 ] reported higher but not significant peritonitis episodes in the RPM group.…”
Section: Clinical Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been found to improve patient's adherence to prescribed therapy, to enhance timely recognition of complications and proactive intervention, to reduce patient's unscheduled access to the hospital and to promote dialysis adequacy. 10,11 These instruments have been well accepted by patients and their family. 12 APD effectiveness has been recently reported also in particular clinical settings such as urgent PD start 13 and treatment of acute kidney injury (AKI).…”
Section: Historical Backgroundmentioning
confidence: 99%